Calcium exerts a strong influence upon phosphohydrolase gene abundance and phylogenetic diversity in soil. (December 2019) - Neal, Andrew L.; Glendining, Margaret J.
Abstract: The mechanisms by which microbial communities maintain functions within the context of changing environments are key to a wide variety of environmental processes. In soil, these mechanisms support fertility. Genes associated with hydrolysis of organic phosphoesters represent an interesting set of genes with which to study maintenance of function in microbiomes. Here, we shown that the richness of ecotypes for each gene varies considerably in response to application of manure and various inorganic fertilizer combinations. We show, at unprecedented phylogenetic resolution, that phylogenetic diversity of phosphohydrolase genes are more responsive to soil management and edaphic factors than the taxonomic biomarker 16S rRNA gene. Available phosphorus – assessed by measuring Olsen-P - exerted some influence on alkaline phosphatase distribution: however, consistent and significant differences were observed in gene abundance between treatments that were inconsistent with bioavailable orthophosphate being the dominant factor determining gene abundance. Instead, we observed gene niche separation which was most strongly associated with soil exchangeable calcium. Our study suggests that the bioavailability of enzyme cofactors (exchangeable calcium in the case of phoD, phoX and βPPhy studied here) influence the abundance of genes in soil microbial communities; in the absence of cofactors, genes coding for alternative enzyme families that do not require the limiting cofactor (for example, non-specific acid phosphatases which require vanadate) become more abundant. Highlights: Metagenomics-based study of the longest running Long-Term Experiment in the World. Studies 16SrRNA-contingent soil communities and nine phosphohydrolase genes. Studies the effect of addition of farmyard manure or inorganic fertilizers. Demonstrates an important role of bioavailable calcium in gene distribution. The influence of bioavailable calcium is greater than bioavailable phosphorus.